THE TRANSFORMATION OF BUSINESS ORGANIZATIONS IN THE DIGITAL ERA: CHANGES IN LEARNING ORGANIZATION AND KNOWLEDGE MANAGEMENT PRACTICES A SYSTEMATIC LITERATURE REVIEW - Umi Masithoh; Agung Nugroho; Luthfi Imam Fahrudi; Wahyu Kurniawan Permadi; Muh Zindi Fahim (CV Naskah Aceh, 2026)
This study aims to examine how digital transformation reshapes learning organization and knowledge management practices in business organizations and to identify the resulting organizational impacts and research gaps. Using a Systematic Literature Review approach guided by the PRISMA 2020 protocol, this study analyses 20 Scopus indexed journal articles published between 2015 and 2025. The review focuses on the concepts of digital transformation, learning organization, and knowledge management within organizational contexts. The findings indicate that digital transformation strengthens continuous learning, digital skill development, and dynamic knowledge flows, while organizational outcomes are most strongly reflected in innovation capability, agility, and adaptability. However, performance effects remain contingent on effective learning and knowledge integration, highlighting persistent conceptual and methodological gaps in the literature.